Methylene blue decolorization fungi from crude oil contaminated soils - Irvan Permana; AMIR AWALUDDIN; SARYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Permana I, Awaluddin A, Saryono. 2019. Methylene blue decolorization fungi from crude oil-contaminated soils. Biodiversitas 20: 2693-2697. One of the world problems is the treatment to remove dyes in textile wastewater. Nowadays, the most effective and compatible method to the environment is decolorization by microorganisms. Therefore, the objective of this study is to find out the best fungi to decolorize synthetic dye methylene blue (MB). Total eight fungi that isolated from crude oil-contaminated soil were analyzed to study the effect of various parameters such as pH, the concentration of dyes, contact times and agitation on their rate of reaction. The initial screening showed that Penicillium sp. FTM7 had greater potential in biodegradation the MB. The optimum decolorization of MB by Penicillium sp. was found after 8 days incubation with agitation 150 rpm and concentration of MB is 40 ppm and unadjusted pH (95.45%). The decolorization of MB was found to follow first-order reactions.